2008
DOI: 10.1123/smej.2.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Sport Sponsorship Activation through a Client-Based Experiential Learning Project

Abstract: Sport management programs continue to focus on developing innovative pedagogical strategies to prepare students to enter and successfully navigate the rapidly evolving, highly competitive sport industry. One effective tactic is to integrate experiential learning projects into the classroom. This paper describes a collaborative three-year partnership involving a sport management program, athletic department, and corporate sponsor. The relationship provided scholarships for the program, internship opportunities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…study abroad) (Shames & Alden, 2005;Younes & Asay, 2003). Experiential learning and metadiscrete experiential learning models have been extensively researched as effective methods of sport management education (Bruening, Madsen, Evanovich, & Fuller, 2010;Hardin, Bemiller, & Pate, 2013;Irwin, Hays & Irwin, 2011;McKelvey & Southall, 2008;Pauline, 2013;Pauline & Pauline, 2008;Pierce, & Petersen, 2010;Southall, Nagel, LeGrande, & Han, 2003;Spence, Hess, McDonald, & Sheehan, 2009;Walker & Lim, 2007), but there is a lack of literature applying the theory to education through athletics.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…study abroad) (Shames & Alden, 2005;Younes & Asay, 2003). Experiential learning and metadiscrete experiential learning models have been extensively researched as effective methods of sport management education (Bruening, Madsen, Evanovich, & Fuller, 2010;Hardin, Bemiller, & Pate, 2013;Irwin, Hays & Irwin, 2011;McKelvey & Southall, 2008;Pauline, 2013;Pauline & Pauline, 2008;Pierce, & Petersen, 2010;Southall, Nagel, LeGrande, & Han, 2003;Spence, Hess, McDonald, & Sheehan, 2009;Walker & Lim, 2007), but there is a lack of literature applying the theory to education through athletics.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The close connection will allow education institutions to identify industry needs [13]. In addition, academic researchers will be able to work with the industry and to develop and enhance the relationship between the academe and business [14,15]. Internships have proven effective in integrating education and work experience and assisting students to transition from a classroom to an actual workplace [16].…”
Section: Introductionmentioning
confidence: 99%
“…In regards to his experiential philosophy to education, Dewey (1916) once stated, "Give the pupils something to do, not something to learn; and the doing is of such a nature as to demand thinking; learning naturally results" (p. 181). For the handful of scholars within sport management that have implemented and studied experiential learning frameworks into their courses (Pauline & Pauline, 2008;McKeylvey & Southall, 2008;Pierce, Petersen, & Meadows, 2011) it is evident that student learning outcomes do tend to be positively impacted, as Dewey had long suggested they would be.…”
Section: Theoretical Framework: Experiential Learning Theorymentioning
confidence: 99%
“…Studies have shown that participation in a client-based project can help students develop real-world skills that are valued by recruiters (Bush, 2009). Examples of client-based projects in sport management are evident in Pauline and Pauline's (2008) Practicum. Practicum experience is defined as a field experience designed to meet specific academic objectives, often in exchange for academic credit.…”
Section: Experiential Learning Practices In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation